The occurrence of mastitis and its impact on selected milk and fertility parameters of dairy cows - Zigo, František; Vasiľ, Milan; Ondrašovičová, Silvia; Zigová, Martina; Kudělková, Lenka (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2020)
Besides reproduction management, one of the important roles of farmers is to control the incidence of diseases during the lactation in dairy herds, especially mastitis. The aim of the study was to evaluate the occurrence of mastitis and its impact on production and fertility indicators in dairy cows’ herd. In herd of 180 dairy cows on the basis of the data provided from milk recording service, 127 cows of Slovak Spotted cattle breed and their crosses with red holstein were included in to the study between 1-2 months after calving. The examination of the health status of mammary gland was consisted from clinical exanimation of udder, assessment of California mastitis test supplemented by the collection of mixed milk samples from each cow and laboratory examination of bacterial pathogens causing mastitis. In addition to the mammary investigation, quantitative and qualitative milk indicators as milk yield, somatic cell count (SCC), percentage of milk fat and protein complemented with fertitlity parameters service period and calving interval were analyzed in the selected dairy cows. Latent (23.6%), subclinical (13.3%) and clinical (4.6%) forms of mastitis were most common in the monitored herd. The most frequently isolated pathogens were coagulase negative staphylococci (54.1%), S. aureus (16.9%), Streptococcus spp. (15.0%), A. viridans (7.5%) and other bacteria (6.4%) from infected milk samples. A reduced milk yield for standardized lactation in cows with clinical and subclinical mastitis was observed, and also was noted an increase SCC in the same groups compared to healthy cows. Among milk qualitative indicators, elevated protein levels in dairy cows with clinical and subclinical form of mastitis have been reported. Decreased milk fat was only observed in dairy cows with clinical mastitis. Comparing the results obtained from fertility indicators an increased and unsatisfactory service period and calving interval in the group of dairy cows with clinical mastitis were recorded. In healthy cows as well as in groups of cows with latent and subclinical mastitis, all reproductive indicators were at optimal levels.